Effectiveness of the STEAM based SETS Learning Model to Increase Student’s Scientific Literacy in Science Learning - Kadir, Dalimawaty; Santosa, Tomi Apra; Iswanto, Iswanto; Marzuki, Kartini; Guna, Bucky Wibawa Karya; Amri, Miftachul; Widodo, Hadi; Suyahman, Suyahman (Edumaspul: Jurnal Pendidikan, 2024)
The purpose of this study was to determine the effectiveness of STEAM-based SETS learning to improve students’ science literacy in science learning. This type of research is a meta-analysis of data collection through the analysis of 11 national and international journals published in 2021-2024. Data sampling techniques through purposive sampling techniques. The inclusion criteria in this study are research accessed through the google scholar database; ERIC, Sciencedirect and Wiley, research related to the STEAM-based SETS model to improve students’ science literacy in science learning, Research must be indexed by SINTA, Scopus and WOS and research has complete data to calculate effect size. Data search keywords are SETS learning models, STEAM, Science literacy and Science learning. Data selection process through PRISMA method. Data analysis is quantitative analysis with the help of Microsoft Excel application. The results concluded that the STEM-based SETS learning model had a significant effect on students’ science literacy skills with an average value of effect size (ES= 0.834) in the high effect size category. The findings provide important information that STEM-based STEM learning modes are effective for improving students’ science literacy in science learning with N-gain = 0.41.